Mutación rara del gen PPOX en un paciente con Porfiria Variegata: reporte de un caso en Perú - Kamimoto-Rodriguez, Augusto (2023)
Introduction: Variegate porphyria (VP) is a rare disease, resulting from mutation of the protoporphyrinogen oxidase (PPOX) enzyme gene, and it is characterized by cutaneous manifestations and acute neuro-visceral symptoms. Case report: We describe the case of a 21-year-old woman from Peruvian highlands. The patient came to the emergency department for abdominal pain, quadriparesis and reddish urine. The patient also presented the syndrome of inappropriate secretion of antidiuretic hormone (SIADH), motor neuropathy and respiratory failure. These clinical features were diagnosed as consequence of a porphyria crisis. The specific diagnosis was made with an elevated urinary porphobilinogen level (185.7 mg/24hours) and genetic analysis, which showed a rare pathogenic variant of the PPOX gene (nucleotide change: c.78C>A and protein change: p.Cys26*). The patient required intensive care until the administration of specific treatment with hemin. Conclusion: We report a case of VP with a pathogenic variant in the PPOX gene.